Thrombosis of Extrasplanchnic and Splanchnic Venous System in Acute Pancreatitis- A Case with Rare Combination of Vascular Complication - Sanjay M Khaladkar; Sai Sabari Vinay Kumar Parripati; Shreeya Goyal; Darshana Dilip; Ajay Dhaiya (Journal of Clinical and Diagnostic Research, 2023)
Vascular complications in acute pancreatitis are common and seen in 25% of cases. While it is common to have venous thrombosis in the Superior Mesenteric Vein (SMV), portal vein, and splenic vein, thrombosis of extra-splanchnic vessels such as Inferior Vena Cava (IVC) and left renal vein due to acute pancreatitis is a rare entity, with more adverse outcomes. A 48-year-old male presented with severe epigastric pain, vomiting, and constipation for seven days. Outside Ultrasonography (USG) report was suggestive of acute pancreatitis. His serum amylase, serum lipase, and D-dimer levels were raised. Computed Tomography (CT) of abdomen and pelvis revealed acute necrotising pancreatitis with peripancreatic fluid collection and thrombosis of splenic vein, left renal vein, and IVC. Thrombosis in pancreatitis can occur due to pancreatic proteolytic enzymes which can cause intimal injury. An enlarged pancreas, walled-off necrosis, and pancreatic pseudocyst can compress veins, resulting in venous stasis. Pancreatitis has a systemic hypercoagulable or prothrombotic state. The patient was given symptomatic treatment along with an injection (inj.) of clexaine and monocef. He showed improvement in 10 days and was symptomatically well on follow-up. Early detection of these findings and targeted treatment for the same is crucial to prevent morbidity and mortality of such patients.